THE ACTUAL QUESTIONS OF INSTRUMENTAL TRAINING IMPROVEMENT OF THE FUTURE MUSIC TEACHER ACCORDING TO THE GUITAR SPECIALIZATION - Kosenko, P.B. (Pedagogy of Higher and Secondary Education, 2007)
The article investigates the questions of students’ preparing in the course of main musical instrument, particularly guitar through the contemporary musical and teaching tendencies.